2011
DOI: 10.1021/np100956k
|View full text |Cite
|
Sign up to set email alerts
|

Labdane Diterpenoids from Leonurus sibiricus

Abstract: Six new labdane diterpenoids, preleosibirone A (1), 13-epi-preleosibirone A (2), isopreleosibirone A (3), leosibirone A (4), leosibirone B (5), and 15-epi-leosibirone B (6), were isolated from the leaves of Leonurus sibiricus. The absolute configurations of 1, 2, 5, and 6 were established by X-ray crystallographic analyses, and leosibirone A (4) was shown to be an artifact of the isolation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
(32 reference statements)
0
31
0
Order By: Relevance
“…In the HMBC spectrum, correlations of H-6 with C-4, C-5, C-7, C-8, C-10, Me-17 with C-7, C-8, C-9, Me-20 with C-1, C-5, C-9, C-10, as well as Me-18 and Me-19 with C-3, C-4, and C-5, were used to assign the hydroxy group to C-6. The known α -orientation of H-5 in labdane diterpenoids (Wu et al, 2011), and the coupling profile (br s) of H-5 and H-6 indicated the cis -arrangement of these two protons in an α -axial, α -equatorial orientation, with the 6-OH β -axially oriented. Thus, the structure of 1 was proposed as 9,13-epoxylabdane-6 β ,15,16-triol.…”
Section: Resultsmentioning
confidence: 98%
“…In the HMBC spectrum, correlations of H-6 with C-4, C-5, C-7, C-8, C-10, Me-17 with C-7, C-8, C-9, Me-20 with C-1, C-5, C-9, C-10, as well as Me-18 and Me-19 with C-3, C-4, and C-5, were used to assign the hydroxy group to C-6. The known α -orientation of H-5 in labdane diterpenoids (Wu et al, 2011), and the coupling profile (br s) of H-5 and H-6 indicated the cis -arrangement of these two protons in an α -axial, α -equatorial orientation, with the 6-OH β -axially oriented. Thus, the structure of 1 was proposed as 9,13-epoxylabdane-6 β ,15,16-triol.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, phytochemical studies on this plant have been reported (Romero-González et al, 2006;Ye et al, 2014;Fuchino et al, 2013;Chang et al, 2010;Moon, 2010;Xiong et al, 2013a,b;Zhang et al, 2013;Peng et al, 2013). Our previous investigation on two plants of the family of Lamiaceae resulted in the isolation of a number of new labdane diterpenes (Wu et al, 2011. In our research on psychoactive natural products from L. japonicus, two diterpenoids were isolated and identified.…”
Section: Introductionmentioning
confidence: 76%
“…Analysis of the 1D- and 2D-NMR spectra revealed that compounds 1 / 2 belong to the bis-spirolabdane class of diterpenoids, which possess a spirotetrahydrofuran ring system. 2531 An exocyclic epoxide ring [δ H 2.28 (1H, d, J = 3.2 Hz)/2.31(1H, d, J = 2.4 Hz), 2.53 (1H, m)/ 2.53 (1H, m); δ C 47.4/47.3 (C-17), 55.9/56.0 (C-8)] was indicated by the HSQC and HMBC (H 2 -17/C-8) correlations. This epoxide ring was placed at C-8 on the basis of its high-field chemical shift (δ C 55.9/56.0) and the HMBC correlations between H 2 -17 [δ H 2.28 (1H, d, J = 3.2 Hz)/2.31(1H, d, J = 2.4 Hz), 2.53 (1H, m)/ 2.53 (1H, m)] and C-7 (δ C 32.4), C-8 (δ C 55.9/56.0), C-9 (δ C 86.2/87.2).…”
Section: Resultsmentioning
confidence: 99%
“…These spectroscopic data suggested that compounds 3 / 4 are bis-spirolabdane diterpenoids possessing a spirotetrahydrofuran ring system. 2531 On the basis of the six degrees of unsaturation, there must be an extra ring in the structures of 3 / 4 . The downfield chemical shift of H-6 (δ H 4.79) suggested that the C-6 hydroxy group was acylated, and therefore a γ -lactone ring between C-6 and C-19 was proposed.…”
Section: Resultsmentioning
confidence: 99%